Danshen improves survival of patients with colon cancer and dihydroisotanshinone I inhibit the proliferation of colon cancer cells via apoptosis and skp2 signaling pathway. (14th September 2017) - Lin, Yin-Yin; Lee, I-Yun; Huang, Wen-Shih; Lin, Yu-Shin; Kuan, Feng-Che; Shu, Li-Hsin; Cheng, Yu-Ching; Yang, Yao-Hsu; Wu, Ching-Yuan
Abstract: Ethnopharmacological relevance: Danshen (Salvia miltiorrhiza Bunge) is widely used in traditional Chinese medicine. However, it's definite clinical effect and mechanism on colon carcinoma is unclear. Aim of the study: To test the hypothesis that the protective effect of danshen on colon cancer and discover the bioactive compounds through in vitro study. Materials and methods: We conducted a nationwide cohort study by using population-based data from the Taiwan National Health Insurance Research Database (NHIRD). The study cohort comprised patients diagnosed with malignant neoplasm of colon (ICD-9-CM codes:153) in catastrophic illness database between January 1, 2000, and December 31, 2010. We used the Kaplan–Meier method to estimate lung cancer cumulative incidences. Next, human colon cancer cells (HCT 116 cells and HT29 cells) were used to investigate the effect of dihydroisotanshinone I (DT) on the proliferation and apoptosis of human colon cancer cells and the underlying mechanism through XTT assay and flow cytometry. The in vivo effect of DT treatment was investigated through a xenograft nude mouse model. Results: In our study, the in vivo protective effect of danshen in the different stage of colon cancer patients was validated through data from the National Health Insurance Research Database in Taiwan. In vitro, we found that dihydroisotanshinone I (DT), a bioactive compound present in danshen, can inhibit the proliferation of colon carcinoma cells, HCT 116 cells and HT-29 cells. Moreover, DT induced apoptosis of colorectal cancer cells. DT also repressed the protein expression of Skp2 (S-Phase Kinase Associated Protein 2) and the mRNA levels of its related gene, Snail1 (Zinc finger protein SNAI1) and RhoA (Ras homolog gene family, member A). In addition, DT also blocked the colon cancer cells recruitment ability of macrophage by decreasing CCL2 secretion in macrophages. DT treatment also significantly inhibited the final tumor volume in a xenograft nude mouse model. Conclusion: Danshen has protective effects in colon cancer patients, which could be attributed to DT through blocking the proliferation of colon cancer cells through apoptosis. Graphical abstract: